Subjetividade sujeitada e prática psicológica: Perspectivas do sujeito da ação - de Souza, Mériti [UNESP]; Munhoz, Sidnei J. [UNESP] (FapUNIFESP (SciELO), 2009)
Research problematizes readings on the so-called subject or agent of action as associated to group constitution and analyzes the implications of such interpretations in psychological practice and in the constitution of subjectivity. The article is based on interdisciplinary readings and on different areas of knowledge so that identity references overlying the modern subject of action may be problematized. Critical emphasis is foregrounded on the classical logic, identity and subjected subjectivity as a-temporal and universal factors of action in the real world. The problematization of subjectivity's construction and its relationships with modes of knowledge will contribute towards the establishment of critical theoretic and strategic interventions.
Subjected subjectivity and psychological practice: Perspectives in agents of action
Keywords: Action; Identity; Psychoanalysis; Psychology; Subjectivity